2021
DOI: 10.1123/jpah.2020-0055
|View full text |Cite
|
Sign up to set email alerts
|

Two Months of Using Global Recommendations for Physical Activity Had No Impact on Cognitive or Motor Functions in Overweight and Obese Middle-Aged Women

Abstract: Background: The effect of globally recommended levels of physical activity on cognition and motor behavior is not completely understood. Therefore, the main aim of this study was to assess the effect of 300 minutes per week of moderate-intensity aerobic exercise on cognitive and motor performance among overweight and obese working-age women. Methods: Overweight and obese participants aged 38–56 years were randomized to either a control or an experimental group performing aerobic exercise at 50% to 60% of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…However, in men, LT was not related to the type of exercise. Several studies are currently looking at associations between PA and cognitive functions [ 4 , 5 , 8 , 12 , 16 , 36 , 37 , 38 ] or learning achievements [ 39 , 40 , 41 , 42 ]. To determine the effectiveness of intuitive thinking and LT, we selected the CRT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in men, LT was not related to the type of exercise. Several studies are currently looking at associations between PA and cognitive functions [ 4 , 5 , 8 , 12 , 16 , 36 , 37 , 38 ] or learning achievements [ 39 , 40 , 41 , 42 ]. To determine the effectiveness of intuitive thinking and LT, we selected the CRT [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing amount of evidence-based research showing that various forms and doses of physical activity (PA) or exercise are effective in combating many chronic diseases [ 1 , 2 ] and improving well-being and mental health [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The health benefits of PA are influenced by age, sex, health, and body mass index (BMI) [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that various forms and intensities of physical activity (PA) are effective in combating many chronic diseases [ 1 , 2 ] and improving wellbeing and mental health [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The health benefits of PA depend on age, gender, health status, and body mass index (BMI) [ 2 , 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence-based research that various forms and doses of PA are effective in combating many chronic diseases [ 1 , 2 , 3 ], improving well-being and mental health [ 4 , 5 , 6 ], improving emotional well-being [ 7 ], and reducing all-cause mortality [ 8 , 9 ]. It was found that the effect of PA on various body functions is quite specific (i.e., depends in a non-linear manner on muscle work intensity, duration, and load “doses”) [ 1 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%